Problems of Capitalization of National Wealth and Distribution of Population by Income Groups in the Republic of Armenia - Markosyan, Ashot; Matevosyan, Elyanora (Bulletin of Yerevan University G: Economics, 2021)
In the current difficult socio-economic conditions and in the presence of a high degree of uncertainty both in the domestic life and in the foreign policy of the Republic of Armenia, revealing the influence of the growth and distribution of incomes of the population on the results of economic growth (taking into consideration also the fact that the value of the national wealth in the Republic of Armenia is not calculated).As known, the main way to increase the income of the population is the growth of the country's GDP, since the calculation of economic growth is based on the volumes of income and production.To describe the relationship between national wealth and GDP, the authors considered the possibility of “capitalizing” GDP and established the necessary period for this. It is obvious that the shorter this period, the more efficiently the country’s economy works, the higher its reproductive potential and the potential for socio-economic development.The article examines the current trends in the formation and distribution of incomes of the population and the state of these relations in the Republic of Armenia. One of the main issues that were in the field of view of the authors was the possibility of a more equitable distribution of GDP, so that a certain fairness of the distribution of income between the owners of labor, capital and the state's income was established. The results of the study showed that the distribution of incomes of the population in Armenia did not contribute to the creation of an atmosphere of social solidarity between different strata of society, but on the contrary. This means that the formation of incomes of different groups of the population in Armenia was unjustified and is a consequence of the unfair distribution of the country's GDP.In the context of the above, the urgent task is to develop recommendations on the methodology for assessing national wealth, the possibilities of its application, as well as the creation of effective, efficient measures and structures for the distribution of national wealth, as well as the income of the population.
Keywords: GDP; national wealth; personal income; income distribution; gross capital formation; assets; investments; produced capital; human capital; natural capital